Growing up with Juvenile Idiopathic Arthritis. Issue 1 (January 2015) - McKeever, Amy; Kelly, Michelle M.
<x xml:space="preserve">Abstract</x> Abstract Juvenile idiopathic arthritis (JIA) is the most common chronic pediatric illness in the United States. The disease encompasses a group of heterogeneous chronic arthritis conditions that begin before age 16 years and persist for more than 6 weeks. Formerly termed juvenile rheumatoid arthritis (JRA), JIA now includes polyarticular, oligoarticular, psoriatic, enthesitis-related arthritis, systematic arthritis, and undifferentiated arthritis. Diagnosis is based on clinical and laboratory features. Treatment includes immunosuppressant therapy, non-steroidal anti-inflammatory drug (NSAIDS), and biologic therapies. This can affect all aspects of an adolescent's life including physiologic, psychosocial, and spiritual components; therefore, this article discusses a comprehensive approach to care management with transition of care as a critical feature in adolescent healthcare.